Tinjauan Maqashid Syariah Pada Bank Digital ( Studi Pada Bank Jago Syariah) - Eniyatul Uyun, Siti (LP2M IAI Miftahul Ulum Pamekasan, 2023)
Sharia Digital Bank is one of the transformations of traditional banking that provides various services by utilizing sharia-compliant technology, namely avoiding Maisir, Riba, Gharar and other things that are not in accordance with sharia principles. This study aims to determine the review of sharia maqashid at Bank Jago Syariah which is one of the Sharia Digital Banks in Indonesia. This research uses a qualitative approach with library research. Where to collect materials related to research sourced from scientific journals, books, articles and others. The results of this study show that Bank Jago Syariah has carried out banking operations with sharia principles and in accordance with the fatwa of DSN-MUI. In the aspect of sharia maqashid principles, Bank Jago Syariah is in accordance with fulfilling the five sharia maqashid, namely, protection of religion, soul, reason, property and turn. This can be seen from the products and services provided by Bank Jago Syariah in accordance with sharia principles and fulfilling the five maqashid.